(untitled) (Third Sector Social Economic Review, 2024)
The aim of the study is to explain the relationship between the consumer confidence index and selected macroeconomic indicators and to examine their effects on each other using Granger Causality and Johansen cointegration tests. Consumer confidence index is revealed by the survey study of the Central Bank of the Republic of Turkey - Electronic Data Distribution System (CBRT-EDDS) and the Turkish Statistical Institute (TURKSTAT).Looking at the answers given in the survey, it was taken into account how much consumers follow psychological factors and macroeconomic indicators. In this regard, the study is important in terms of shedding light on behavioral economics and revealing which macroeconomic indicators consumers follow. The selected macroeconomic indicators are those that are thought to be followed closely by consumers. Accordingly, the data used in the analysis covers the period 2014:01-2023:06. As a result of the analysis, consumer confidence index (CCI); While the domestic producer price index (D-PPI1), consumer price index (CPI1) and unemployment were the cause, the exchange rate was found to be the cause of CCI.